To write is to choose ang kasaysayan ng College Editors Guild of the Philippines, 1931-1972 - Madula, Rowell Decena; Cahiles, Gerg Anrol Rubio (Manila De La Salle University Publishing House, 2012)
History of the College Editors Guild of the Philippines, an organization of student journalists and student publications advocating for press freedom.
Includes bibliographical references (pages 162-176) and index.
In Filipino.
Keywords: College student newspapers and periodicals -- History. -- Philippines